2004
DOI: 10.1073/pnas.0402251101
|View full text |Cite
|
Sign up to set email alerts
|

Estimating genome conservation between crop and model legume species

Abstract: Legumes are simultaneously one of the largest families of crop plants and a cornerstone in the biological nitrogen cycle. We combined molecular and phylogenetic analyses to evaluate genome conservation both within and between the two major clades of crop legumes. Genetic mapping of orthologous genes identifies broad conservation of genome macrostructure, especially within the galegoid legumes, while also highlighting inferred chromosomal rearrangements that may underlie the variation in chromosome number betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
305
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 424 publications
(335 citation statements)
references
References 37 publications
19
305
1
3
Order By: Relevance
“…M. truncatula and alfalfa share highly conserved nucleotide sequences and exhibit nearly perfect synteny between the two genomes (Choi et al, 2004a). Although the pea genome is approximately 10 times larger than that of M. truncatula and has one less chromosome, the colinearity of genes is also remarkably conserved between the two genomes, with major evident differences being inferred interchromosomal rearrangements (Choi et al, 2004b). It was suggested that chromosomal rearrangements involving Medicago (alfalfa and M. truncatula) chromosome 6 might be responsible for the difference in chromosome number between Medicago and pea (Choi et al, 2004b;Kalo et al, 2004).…”
Section: Macrosynteny Among Papilionoid Legumesmentioning
confidence: 94%
See 3 more Smart Citations
“…M. truncatula and alfalfa share highly conserved nucleotide sequences and exhibit nearly perfect synteny between the two genomes (Choi et al, 2004a). Although the pea genome is approximately 10 times larger than that of M. truncatula and has one less chromosome, the colinearity of genes is also remarkably conserved between the two genomes, with major evident differences being inferred interchromosomal rearrangements (Choi et al, 2004b). It was suggested that chromosomal rearrangements involving Medicago (alfalfa and M. truncatula) chromosome 6 might be responsible for the difference in chromosome number between Medicago and pea (Choi et al, 2004b;Kalo et al, 2004).…”
Section: Macrosynteny Among Papilionoid Legumesmentioning
confidence: 94%
“…Although the pea genome is approximately 10 times larger than that of M. truncatula and has one less chromosome, the colinearity of genes is also remarkably conserved between the two genomes, with major evident differences being inferred interchromosomal rearrangements (Choi et al, 2004b). It was suggested that chromosomal rearrangements involving Medicago (alfalfa and M. truncatula) chromosome 6 might be responsible for the difference in chromosome number between Medicago and pea (Choi et al, 2004b;Kalo et al, 2004). Interestingly, the same chromosome seems to have also been associated with the interchromosomal rearrangements between M. truncatula and chickpea (H. Zhu and D. Cook, unpublished data).…”
Section: Macrosynteny Among Papilionoid Legumesmentioning
confidence: 99%
See 2 more Smart Citations
“…They allow evaluation of a large number of genotypes quickly and have been used to identify parental stock for soybean breeding (Bianchi-Hall et al 1998;Campbell and Carter 1990;Carter and Rufty 1993;Spehar 1994;Bianchi-Hall et al 2000;Silva et al 2001). Common bean and soybean both pertain to the tribe Phaseoleae, much more closely related to each other than they are to Lotus, Medicago, or other grain legumes such as lentils or chickpeas (Choi et al 2004). This opens the possibility of common genes and/or mechanisms between the species, and suggests that the application of methods used in soybean might serve to discriminate genetic differences in common bean as well.…”
Section: Introductionmentioning
confidence: 99%